Past and Current European Monetary Union Crises: Lessons for the Envisaged West African Monetary Union - Nkwatoh, louis Sevitenyi; Abdullahi, Yahya Zakari; Aliyu, Chika Usman (International Journal of Economics and Financial Issues, 2019)
The Economic Community of West African States (ECOWAS) is committed to forming a broader monetary union by 2020. The approach of forming the union is a replica of the European-type monetary union, which is predicated on the optimum currency area (OAC) theory. All the monetary unions that were created among European sovereign States within the last half of the eighteenth century, collapsed due to political and economic differences. Currently, the European monetary union (EMU) is unstable due to ongoing crises, which may not be a good signal for West African States, whose economies are persistently being hit by asymmetric shocks. This study therefore, analysed the economies of West African States within the context of the OAC theory, and further examined whether the past and current EMUs provide any lessons for ECOWAS. The analyses show that ECOWAS economies have not met the OAC theory, implying that the European-type monetary union crises might manifest in the ECOWAS region. To avert such crises in the envisaged West African monetary union, member countries must be compelled to satisfy the OAC criteria before ascending onto the union, and the governments of ECOWAS should lay more emphasizes on the political will and fiscal discipline of the respective member countries. Keywords: European Monetary Unions, Optimum Currency Area, Economic Community of West African States JEL Classifications: F15, F2, F33, F45 DOI: https://doi.org/10.32479/ijefi.8231